Technological grandparents: how communication technologies can improve the well-being of the elderly? - Corti, Laura; Brizi, Maria Rosaria; Pennacchini, Maddalena; Bertolaso, Marta (AI & society, 2024)
The ageing of the population is one of the most significant social transformations that the twenty first century is showcasing and a challenge that impacts society at large. The elderly, inasmuch as everybody else, are confronted with continuous transformations that are induced by technology, although they seldom benefit from the opportunities that technology entails. The digital divide amongst various segments of the population is often age-related and due to different reasons, including biological, psychological, social and financial ones. There is an ongoing reflection pertaining to the factors that hinders the full adoption of ICTs by the elderly and a question regarding what can be done to overcome their poor involvement in technology. This article, based on the results of a recent research, which has been conducted in Italy, aims at highlighting the importance of engaging the elderly in the use of technology as a key to building bridges between generations.